Crystallization Behavior of Se85Cd8Zn7 Chalcogenide Glass - Omar A. Lafi (Jordan Journal of Physics, 2025)
Ternary Se85Cd8Zn7 chalcogenide glass was prepared by melt quenching technique. Experimental measurements by differential scanning calorimeter (DSC) are used for studying crystallization behavior of this glass under non-isothermal conditions. DSC curves show well defined endothermic and exothermic peaks at glass transition (Tg) and crystallization peak (Tc) temperatures. The Tc dependence on the heating rate (β) is utilized in the determination of the crystallization activation energy (Ec) and the Avrami exponent (n). These crystallization parameters were deduced using Kissinger, Takhor, Augis-Bennett and Ozawa-Matusita methods. The theoretical derivations of these methods were discussed in this work. The resulting values of Ec obtained from the different methods agree good with each other and the obtained value of Avrami exponent (n = 0.87) indicated that the crystal growth in Se85Cd8Zn7 glass occurs in one dimension. Keywords: Chalcogenide glasses; Differential scanning calorimeter (DSC); Crystallization activation energy; Dimensionality of crystal growth.